Image of nurses in Chile through children's drawings: An iconographic study - Edgardo Álvarez-Muñoz; Gerak Aguilar-Valdivia; Edith Rivas-Riveros; Catalina Sepúlveda-Rivas (Universidade Federal do Rio de Janeiro, 2024)
Abstract Objective To reveal the image of nursing professionals in Chile through the analysis of children's drawings. Method This is an exploratory qualitative study, involving the collection of information through nine drawings made by children aged between 7 and 10 years, using free technique, and then were analyzed with the Iconographic Method proposed by Erwin Panofsky. Results Most drawings depict clinical activities of nurses, focusing predominantly on the technical dimension of the profession. Although nursing is commonly associated with a mostly female occupation, permeated by gender stereotypes, some participants were able to identify the presence and importance of the male role in this professional field. No iconographic elements were identified that would reinforce stigmas associated with nursing professionals, such as the view that they are supporters, aides, or mere medical assistants. Conclusions and implications for practice Children's drawings serve as a reflection of the collective imagination of society. By studying them in relation to nursing, we can identify the advances of the profession and glimpse its near future. This research contributes to understanding the current image of the profession in society, and allows an analysis that goes further, helping to establish future directions and the evolution of this collective perception.